The shift of the microbial community in activated sludge with calcium treatment and its implication to sludge settleability. (May 2016) - Ye, Chengchen; Yang, Xinping; Zhao, Fang-Jie; Ren, Lifei
Highlights: Ca 2+ addition improved the settleability and metabolic reactivity of the sludge. Ca 2+ changed microbial communities and structures of the sludge in reactors. Ca 2+ increased the production of the EPS and facilitated the development of floc. Abstract: The sludge settleability is of prime importance for the activated sludge process. The effect of calcium ion on the biological performance of sludge was investigated in a lab-scale activated sludge system with varying Ca 2+ concentration. Results indicated that addition of 150 mg/L Ca 2+ to the influent significantly improved the settling characteristics and metabolic reactivity of activated sludge in the bioreactors. Analyses using denaturing gradient gel electrophoresis (DGGE) and 16S rRNA sequencing showed that a significant difference in the presence of certain bacterial groups between the sludge systems with 150 mg/L Ca 2+ and those with 0–100 mg/L Ca 2+ addition. Ca 2+ also increased the production of the extracellular polymeric substance (EPS) and facilitated the development of microbial cluster in the bioreactor. Study showed that an addition of 150 mg/L Ca 2+ to the influent provides a simple approach to improve the settling properties of activated sludge and maintain high pollutant removal efficiency.